Determination of MDA as oxidative stress marker and most common type of blood group in asthmatic patients before and after treatment with montelukast drug. - Jwad Ali Saleh; Shakir Mahmoud Suleiman; Zaidan Jayed Zaidan (Tikrit Journal of Pure Science, 2023)
Asthma is a complex chronic inflammatory disorder of airways characterized by airway smooth muscle hypertrophy, hyperplasia and over production of mucous in which many cells and cellular elements play an important role.